A Stereomicroscopic Analysis of Dentinal Micro Cracks after Root Canal Preparation Using Four Different Rotary Instruments. - Samar Abdul-Hamed1, Rasha H Jehad1, Zainab M. Abdul-Ameer1, Jacob Al-Hashemi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A variety of single-engine driven files and kinematics have been introduced to improve the clinical performance of NiTi rotary files. The purpose of this in vitro study was to measure and compare the incidence of dentinal defects after root canal preparation with different single file systemsA variety of single-engine driven files and kinematics have been introduced to improve the clinical performance of NiTi rotary files. The purpose of this in vitro study was to measure and compare the incidence of dentinal defects after root canal preparation with different single file systems